2008
DOI: 10.1093/brain/awn268
|View full text |Cite
|
Sign up to set email alerts
|

Specific relations between neurodevelopmental abilities and white matter microstructure in children born preterm

Abstract: Survivors of preterm birth have a high incidence of neurodevelopmental impairment which is not explained by currently understood brain abnormalities. The aim of this study was to test the hypothesis that the neurodevelopmental abilities of 2-year-old children who were born preterm and who had no evidence of focal abnormality on conventional MR imaging were consistently linearly related to specific local changes in white matter microstructure. We studied 33 children, born at a median (range) gestational age of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
195
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(210 citation statements)
references
References 47 publications
(52 reference statements)
11
195
1
3
Order By: Relevance
“…At near-term age, the genu and splenium of the CC have not yet myelinated (29), although posterior aspects (splenium) develop earlier than anterior (genu) aspects (16,30). Lesion studies indicate that genu WM mediates motor coordination (31), and prior studies reported neonatal CC WM structure associated with future motor function (32,33), consistent with our findings.…”
Section: Corpus Callosumsupporting
confidence: 87%
“…At near-term age, the genu and splenium of the CC have not yet myelinated (29), although posterior aspects (splenium) develop earlier than anterior (genu) aspects (16,30). Lesion studies indicate that genu WM mediates motor coordination (31), and prior studies reported neonatal CC WM structure associated with future motor function (32,33), consistent with our findings.…”
Section: Corpus Callosumsupporting
confidence: 87%
“…Not surprisingly, preterm birth is associated with impaired brain development reflected in reduced brain volumes, diminished cortical gyrification and delayed maturation of gray and white matter structures (Ball et al, 2012;Keunen et al, 2012;Rathbone et al, 2011;Shimony et al, 2016;Volpe, 2009). These deficits are also present in the absence of focal brain injury and have been noted to persist through childhood (Counsell et al, 2008;Fischigómez et al, 2015;Monson et al, 2016). Behavioral sequelae of these structural disturbances in brain development are observed across a wide spectrum of neurodevelopmental outcomes and include cognitive delay, working memory impairment, learning disabilities, executive functioning deficits, internalizing and externalizing behavioral problems and developmental psychopathology including autism and attention deficit hyperactivity disorder (Fischi-gómez et al, 2015;Johnson et al, 2010Johnson et al, , 2009Monson et al, 2016;Urben et al, 2015).…”
Section: Preterm Birthmentioning
confidence: 99%
“…Counsell et al 51 found linear correlations between the developmental quotient and fractional anisotropy values in the corpus callosum and right cingulum, between performance subscores and fractional anisotropy in the corpus callosum and right cingulum, and between hand-eye coordination scores and fractional anisotropy in the cingulum, fornix, anterior commissure, corpus callosum, and right uncinate fasciculus in 2-year-old children born preterm. Similarly, fractional anisotropy values in the left anterior uncinate fasciculus in school-age children born preterm were correlated with the Wechsler Intelligence Scale for Children Verbal IQ, Wechsler Intelligence Scale for Children Full-scale IQ, and Peabody Picture Vocabulary TestRevised scores for preterm groups at 12 years of age.…”
Section: Review 335mentioning
confidence: 99%